Principles of information systems security : - Dhillon, Gurpreet (John Wiley & Sons, 2007)
The real threat to information systems security comes from people, not computers. That’s why students need to understand both the technical implementation of security controls, as well as the softer human behavioral and managerial factors that contribute to the theft and sabotage of proprietary data.